Trophic Ecology of Humpback Whales (Megaptera novaeangliae) in the Magellan Strait as Indicated by Carbon and Nitrogen Stable Isotopes - Haro, Daniela; Riccialdelli, Luciana; Acevedo, Jorge; Aguayo-Lobo, Anelio; Montiel San Martin, Americo Manuel (My University, 2016)
The contribution of prey species to the diet and their variation over time are poorly understood processes in the trophic ecology of Southeast Pacific humpback whales (Megaptera novaeangliae). The purpose of this study was to use carbon and nitrogen stable isotopes to provide insights into the trophic ecology and to determine the inter-annual variation of the diet of the humpback whales in the Magellan Strait. During 2011 and 2012, an analysis was carried out to determine the isotopic composition of humpback whale skin. We used a Bayesian isotope mixing model to determine the relative contribution of prey species to the isotopic value of the consumer. The humpback whale had mean values of-16.3 +/- 0.6%c in delta C-13 and 14.7 +/- 1.0 parts per thousand in delta N-15 (n = 33). The delta C-13 and delta C-13 in both the whales and the Fuegian sprat (Spratrus fueguensis) were significantly higher in 2011 compared to 2012. Additionally, females had significantly higher delta N-15 values in 2012; however, mean delta C-13 and delta N-15 values of whales within each season and between age classes did not differ statistically. A variation was observed in the contribution of different prey to the whale diet between the study years, with Fuegian sprat as the predominant prey during 2011 (mean 55 +/- 12%), and crustaceans dominating the diet in 2012 (mean 82 +/- 9%). This study confirms the diet of the humpback-whale within the Magellan Strait. Furthermore, isotopic analyses suggest important inter-annual changes due to (1) changes in the proportion of the species being consumed, probably due to variations in availability (e.g., abundance) of prey; and/or (2) annual isotopic changes at the base of the food web. Further studies are required on the population dynamics of prey in order to monitor annual changes in abundance and food supply.
Keywords: southeast pacific humpback whale; megaptera novaeangliae; diet; francisco coloane; coastal marine protected area; fuegian sprat; sprattus liteguensis lobster krill; munida gregaria; krill; euphausia lucens